The Fatty Liver Index (FLI) Relates to Diabetes-Specific Parameters and an Adverse Lipid Profile in a Cohort of Nondiabetic, Dyslipidemic Patients. (19th May 2017) - Leutner, Michael; Göbl, Christian; Schlager, Oliver; Charwat-Resl, Silvia; Wielandner, Alice; Howorka, Eleonora; Prünner, Marlies; Bozkurt, Latife; Maruszczak, Katharina; Geyik, Hacer; Prosch, Helmut; Pacini, Giovanni; et al.
ABSTRACT: Background : Patients with hyperlipidemia are at high risk for developing a fatty liver. The fatty liver index (FLI) is a noninvasive and well-established method for the estimation of a fatty liver. However, little is known about the metabolic characterization of nondiabetic treated patients with hyperlipidemia who have different risk levels for a fatty liver. Methods : In this study, 74 nondiabetic patients with hyperlipidemia were divided into 3 groups according to their fatty liver index. A comparison of metabolic characteristics was done. These characteristics included intima media thickness (IMT) and nutritional habits, which were further divided into FLI subgroups with low, intermediate, and high risk for a fatty liver. Results : Patients with hyperlipidemia, with a high risk for a fatty liver (FLI ≥ 60), had subclinical elevations in parameters of carbohydrate metabolism (insulin, fasting plasma glucose, C-peptide) including a higher insulin resistance (quantitative insulin sensitivity check index, QUICKI) compared to lower FLI groups. These patients also presented a higher risk for a metabolic syndrome ( p = 0.018), as well as an adverse lipid profile (e.g., high-density lipoprotein [HDL] cholesterol, triglycerides [TG]–HDL ratio). FLI group 3 was characterized by significantly lower levels of omega-3 fatty acids ( p = 0.048). Conclusion : The fatty liver index relates to diabetes-specific parameters and an adverse lipid profile and is an appropriate index for risk evaluation of metabolic syndrome.